Experimental Inoculation of Young Calves with SARS-CoV-2 - Shollie Falkenberg; Alexandra Buckley; Melissa Laverack; Mathias Martins; Mitchell V. Palmer; Kelly Lager; Diego G. Diel (Viruses, 2021)
The host range of SARS-CoV-2 and the susceptibility of animal species to the virus are topics of great interest to the international scientific community. The angiotensin I converting enzyme 2 (ACE2) protein is the major receptor for the virus, and sequence and structural analysis of the protein has been performed to determine its cross-species conservation. Based on these analyses, cattle have been implicated as a potential susceptible species to SARS-CoV-2 and have been reported to have increased ACE2 receptor distribution in the liver and kidney, and lower levels in the lungs. The goal of the current study was to determine the susceptibility of cattle to SARS-CoV-2 utilizing inoculation routes that facilitated exposure to tissues with increased ACE2 receptor distribution. For this, colostrum-deprived calves approximately 6 weeks of age were inoculated via the intratracheal or intravenous routes. Nasal and rectal swab samples, as well as blood and urine samples, were collected over the course of the study to evaluate viral shedding, viremia, and seroconversion. Pyrexia was used as the primary criteria for euthanasia and tissue samples were collected during necropsy. Importantly, SARS-CoV-2 RNA was detected in only two nasal swab samples collected on days 3 and 10 post-inoculation (pi) in two calves; one calf in the intratracheal group and the other calf in the intravenous group, respectively. Additionally, the calf in the intratracheal group that was positive on the nasal swab on day 3 pi also had a positive tracheobronchial lymph node on day 9 pi. Viral nucleic acid load on these samples, based on PCR cycle threshold values, were low and infectious virus was not recovered from the samples. These results suggest that there was no productive replication of SARS-CoV-2 in calves following intratracheal and intravenous inoculation.